Transformasi Pemasaran Digital BUMDES Pengolahan Pakan Ikan Terapung Berbasis Blue Economy sebagai upaya peningkatan Produk Unggulan Desa - Rasyidin, M; Saleh, M; Azmi, Dasril; Rizal, Muhammad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The partner in this community service activity is BUMDES Malaka, a village-owned enterprise from Jangka Alue Bie that produces floating fish feed. BUMDES Malaka was established in 2016, and the management is elected by the community through a village deliberation forum. The main objective of establishing BUMDES Malaka is to meet the needs of fish farmers and provide an alternative solution for farmers to obtain cheaper and higher-quality fish feed, as previously, fish feed was sourced from outside the province at high prices. To enhance the partner's capacity, training in digital marketing, as well as improvements in management and production quality, are necessary. The methods used in this service activity include training and hands-on practice. The outcomes of this activity include an increase in the knowledge of BUMDES Malaka's management in the field of digital marketing and an improvement in the partner's capabilities in business management.